2008
DOI: 10.1007/s10620-008-0199-9
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Effect of Irsogladine Maleate Against Indomethacin-Induced Small Intestinal Lesions in Rats

Abstract: The effect of irsogladine maleate, a widely used antiulcer drug in Japan, on indomethacin-induced small intestinal lesions was examined in rats. Animals without fasting were given indomethacin (10 mg/kg, s.c.) and sacrificed 24 h later. Irsogladine (1-10 mg/kg) or 16,16-dimethyl prostaglandin E2 (dmPGE2 0.03 mg/kg) was given p.o. twice, 0.5 before and 6 h after indomethacin, while ampicillin (800 mg/kg) was given twice, 18 and 0.5 h before. Indomethacin caused severe lesions in the small intestine, mainly the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 30 publications
5
31
0
Order By: Relevance
“…PAS staining increased with lafutidine, roxatidine, and irsogladine (Fig. 5) pretreatment as described in previous reports [56,57]. These results suggest that different inhibitory mechanisms may be operating with these effective drugs.…”
Section: Prevention and Treatment Of Small Intestinal Mucosal Injury supporting
confidence: 86%
“…PAS staining increased with lafutidine, roxatidine, and irsogladine (Fig. 5) pretreatment as described in previous reports [56,57]. These results suggest that different inhibitory mechanisms may be operating with these effective drugs.…”
Section: Prevention and Treatment Of Small Intestinal Mucosal Injury supporting
confidence: 86%
“…Since lafutidine was found to prevent bacterial invasion, probably by up-regulating Muc2/mucus expression, it would be understandable that this agent suppressed the increase of iNOS expression in the small intestine following loxoprofen treatment. We previously reported that the mucosal protective drugs, such as irsogladine, rebamipide and teprenone, all significantly increased mucus secretion and suppressed bacterial invasion and iNOS expression, thereby reduced the severity of intestinal lesions produced by indomethacin [33]. These results together support a causeeffect relationship between changes in the above three events; ie., mucus secretion, bacterial invasion, and iNOS expression.…”
Section: Commentarysupporting
confidence: 61%
“…To produce injury to the stomach, IM is usually injected to fasting rats or mice (Kato et al 2009;Rios et al 2010;Zelena and Filaretova 2010). On the contrary, for induction of injury to the small intestine IM is injected to fed animals (Kamei et al 2008;Yoda et al 2010;Kawahara et al 2011). The results of the present and our previous ) studies demon- strate that a single IM injection to fasting rats at gastric ulcerogenic dose may sequentially induce damage to the stomach and then, after refeeding, to the small intestine as well.…”
Section: Discussionmentioning
confidence: 51%